Adapting to Novel Environments Together: Evolutionary and Ecological Correlates of the Bacterial Microbiome of the World’s Largest Cavefish Diversification (Cyprinidae, Sinocyclocheilus) - Zhou, Shipeng; Rajput, Amrapali P.; Mao, Tingru; Liu, Yewei; Ellepola, Gajaba; Herath, Jayampathi; Yang, Jian; Meegaskumbura, Madhava (Frontiers in Microbiology, 2022)
The symbiosis between a host and its microbiome is essential for host fitness, and this association is a consequence of the host’s physiology and habitat. Sinocyclocheilus, the largest cavefish diversification of the world, an emerging multi-species model system for evolutionary novelty, provides an excellent opportunity for examining correlates of host evolutionary history, habitat, and gut-microbial community diversity. From the diversification-scale patterns of habitat occupation, major phylogenetic clades (A–D), geographic distribution, and knowledge from captive-maintained Sinocyclocheilus populations, we hypothesize habitat to be the major determinant of microbiome diversity, with phylogeny playing a lesser role. For this, we subject environmental water samples and fecal samples (representative of gut-microbiome) from 24 Sinocyclocheilus species, both from the wild and after being in captivity for six months, to bacterial 16S rRNA gene profiling using Illumina sequencing. We see significant differences in the gut microbiota structure of Sinocyclocheilus, reflective of the three habitat types; gut microbiomes too, were influenced by host-related factors. There is no significant association between the gut microbiomes and host phylogeny. However, there is some microbiome related structure at clade level, with the most geographically distant clades (A and D) being the most distinct, and the two overlapping clades (B and C) showing similarities. Microbes inhabiting water were not a cause for significant differences in fish-gut microbiota, but water quality parameters were. Transferring from wild to captivity, the fish microbiomes changed significantly and became homogenized, signifying adaptability and highlighting the importance of environmental factors (habitat) in microbiome community assembly. The core microbiome of this group closely resembled that of other teleost fishes. Our results suggest that divergent selection giving rise to evolutionary novelties also includes the microbiome of these fishes, which provides a functional advantage for life in the resource-depleted cave environment.